Philanthropy and Settler Colonialism - O'Brien, A. author. aut Link
VIII, 304 p.
Keywords: This book, the first long-range history of the voluntary sector in Australia and the first internationally to compare philanthropy for Indigenous and non-Indigenous peoples in a settler society, explores how the race and gender ideologies embedded in philanthropy contributed to the construction of Australia's welfare state.